Advances in Resist Materials and Processing Technology XXVI 2009
DOI: 10.1117/12.814223
|View full text |Cite
|
Sign up to set email alerts
|

Underlayer designs to enhance the performance of EUV resists

Abstract: Extreme ultraviolet (EUV) lithography has gained momentum as the method of choice for <32-nm half-pitch device fabrication. In this paper, we describe our initial attempts to increase an EUV resist's sensitivity without compromising resolution and line roughness via introduction of a thermally crosslinkable underlayer. The main purpose is to test the possibility of using a combination of photoacid generators (PAGs) and EUV sensitizers (phenol type) in the underlayer designs to enhance the overall performance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Added benefits to underlayer stacks can include LER reduction of the resist patterns, increased process latitude and improved etch selectivity during the pattern transfer process. 24 The propagation of striations or roughness from the resist into the hardmask during the pattern transfer process is a concern. This is thought to be the result of having inadequate resist thicknesses and/or inadequate etch resistance.…”
Section: Underlayer Contribution To Roughnessmentioning
confidence: 99%
“…Added benefits to underlayer stacks can include LER reduction of the resist patterns, increased process latitude and improved etch selectivity during the pattern transfer process. 24 The propagation of striations or roughness from the resist into the hardmask during the pattern transfer process is a concern. This is thought to be the result of having inadequate resist thicknesses and/or inadequate etch resistance.…”
Section: Underlayer Contribution To Roughnessmentioning
confidence: 99%
“…In particular, the EUV community has been publishing extensively on the use of bottom coats that substantially improve their materials performance 17,18 . Although there are defect questions that make these approaches less attractive, they are areas that one must consider if we are going to approach the needed capabilities of the future.…”
Section: Ancillary Chemicals and Processes Including CDLmentioning
confidence: 99%
“…The use of underlayers to enhance the imaging properties of EUV resist is now an area of active exploration [14][15][16] sensitivity. Looking at the details of the resist to substrate interface [17], has also suggested that interface properties may be playing a significant role in LER and thus that underlayers might be able to mitigate these effects.…”
Section: Interface Effectsmentioning
confidence: 99%